Science, faith and the climate crisis - Myers, Sally; Hemstock, Sarah; Hanna, Edward (Emerald Publishing Limited, 2020)
Inspired by a 2019 conference, Moana Water of Life, and including real-life insights from a diverse range of participants, this book showcases the potential fruits of open dialogue between stakeholders to navigate the critical challenges to planetary health caused by the climate crisis. The Earth's climate is changing faster than at any point in the history of modern civilisation through human-induced global warming, yet public reactions to this scientific truth remain dissonant. Inspired by a 2019 conference, Moana Water of Life, this book showcases the challenges and potential fruits of an open dialogue between stakeholders to navigate the critical challenges to planetary health caused by the climate crisis. Inviting participants to contribute 'in their own voices', this book cuts across real-life insights, ranging from researchers from the Pacific Islands Region on the front line of devastating water surpluses and shortages, to the thoughts of leading climate change and Earth scientists, social scientists, educators, faith leaders, theologians and activists who are offering practical solutions to the problem. By highlighting this collection of inspiring stories at the local and global levels, the authors offer a vision of hope for communities in the future to communicate, adapt to change and ultimately resist further deterioration of the planet's health. All royalties from this book are being donated to the Red Cross in the Pacific Island Region.
Foreword / Archbishop Justin Welby -- Preface / Bishop David -- Chapter 1.Christianity, Kiribati, and climate change induced migration / Fetalai Gagaeolo, Sarah Hemstock and Conner Price -- Chapter 2. Moana:'Oku mafeia he 'Otua 'a e me' a kotoa pe (Moana: Nothing is impossible with God) / Peni Hausia Havia -- Chapter 3. The rivers of humankind / Mark Macklin and John Lewin -- Chapter 4. Earth, air, fire and ice: exploring links between human-induced global warming, polar ice melt and local scale extreme weather / Edward Hanna and Richard Hall -- Chapter 5. Climate change and the role of education / Sarah Hemstock, Siu Jione, Mark Charlesworth, Patrina Dumaru -- Chapter 6.Towards citizen governance for climate education and justice: a science-policy perspective / Andrew Kythreotis and Theresa Mercer -- Chapter 7. Ocean of love: science, policy and spirituality of the water crisis / Marc Handley Andrus -- Chapter 8. Reading the Bible as waters rise: ecological interpretation of scripture / Emily Colgan -- Chapter 9. Reaching 'net zero': an energy perspective / Mike Colechin -- Chapter 10. Sustainislandhome.org: an app for climate action and advocacy / Sheila Andrus -- Chapter 11. Faith in action at the United Nations: a confluence of rivers / Lynnaia Main -- Chapter 12. Different voices: one call / Sally Myers -- Afterword / Archbishop Winston Halapua.
Includes index.
Print version record.
Keywords: Climatic changes -- Pacific Ocean; Religion and science -- Pacific Ocean; Planetary quarantine; Science, Global Warming & Climate Change; Climate change